Atomic scale structural characterization of B2 phase precipitated along FCC twin boundary in a CoCrFeNiAl0.3 high entropy alloy. (15th March 2019) - Wang, Xiaodong; Zhou, Wei; Liu, Pan; Song, Shuangxi; Reddy, Kolan Madhav
Abstract: We report atomic scale structural characterization of the phase separation along the twin boundary in a CoCrFeNiAl0.3 high entropy alloy on being subjected to intermediate temperature annealing after introducing sufficient dislocations by tensile deformation. Transmission electron microscopy revealed that the nucleation of B2 phase is associated with the reaction between the dislocations and twin boundaries. The configuration of the B2 phase shows that two different partially coherent interfaces result in an asymmetric nucleus growing into one side of the twinning. Graphical abstract: Unlabelled Image